A New Extension of the Rectangular b-Metric Spaces. (1st June 2020) - Mlaiki, Nabil; Hajji, Mohamed; Abdeljawad, Thabet
Abstract : In this paper, we introduce a generalization of rectangular b -metric spaces, by changing the rectangular inequality as follows: D ζ a, b ≤ ζ a, b, u, v D ζ a, u + D ζ u, v + D ζ v, b, for all distinct a, b, u, v ∈ X . We prove some fixed point theorems, and we use our results to present a nice application in the last section of this paper.